Seismic Resilience of Steel-Braced Frames Incorporating Steel Slit Dampers: A Review and Comparative Numerical Analysis - Zaid A. Al-Sadoon; M. Almohammad-albakkar (Civil Engineering Journal, 2024)
Steel dampers, specifically steel slit dampers (SSDs), are crucial for enhancing the seismic resilience of buildings by absorbing energy and mitigating damage. SSDs are celebrated for their ability to produce stable hysteretic behavior, owing to the inelastic deformation of their strips, alongside benefits such as lightness, ease of manufacture, and straightforward post-earthquake replacement. This research extensively examines SSD applications, design principles, and innovations in their modeling, optimization, and production processes. The literature highlights SSDs' consistent performance in resisting both compression and tension, their adaptability in strength, ductility, and energy dissipation through modifications in strip configurations and the superiority of non-prismatic and hourglass-shaped designs over traditional options. Numerical analyses have been conducted to assess the effectiveness of non-prismatic slit dampers in comparison to their prismatic counterparts within braced frames. Three distinct braced frame configurations have been analyzed: one with a diagonal brace without a damper, another featuring a uniform prismatic slit damper, and a third incorporating a non-prismatic slit damper with an hourglass shape. The analysis primarily compared these systems' hysteresis behavior, ductility, and energy dissipation capacities. Results indicate a significant enhancement in performance when utilizing non-prismatic slit dampers. Notably, these dampers exhibited a remarkable 69% increase in cumulative energy dissipation compared to prismatic ones. Furthermore, the study reveals that a steel slit damper-braced frame, when equipped with optimally designed slit geometries, can tolerate inter-story drifts in excess of 2% while simultaneously achieving a greater than 12% increase in energy dissipation efficiency. Doi: 10.28991/CEJ-2024-010-04-019 Full Text: PDF